TAMANHO DE PARCELA PARA ENSAIOS DE MILHO VERDE - Alves, Sueli Martins de Freitas; Seraphin, JosÃ© Carlos; Seraphin, JosÃ© Carlos; Zimmermann, Francisco JosÃ© P.; Zimmermann, Francisco JosÃ© P.; Silva, Ãlvaro EleutÃ©rio da; Silva, Ãlvaro EleutÃ©rio da (REVISTA DE AGRICULTURA, 2015)
TAMANHO DE PARCELA PARA ENSAIOS DE MILHO VERDE